Match running performance in male professional soccer players: Interactive effect of score-line and playing position - Ventura, A. P.; Teixeira, A. S.; Teixeira, R. M.; De Aquino, R. L. Q. T.; De Sousa Neto Segundo, J. F.; Silva, C. H. A.; Cetolin, T.; Mohr, P. A.; Da Silva, J. F. (Journal of Physical Education and Sport, 2024)
Time-motion analysis has grown substantially in recent decades with the aim of monitoring players' work rate profiles during a match. This study investigated how current score-line (i.e. winning, drawing, losing) and playing position interact to influence match running performance (i.e. total distance, and the distances covered at different intensities) in male professional soccer players. A total of 193 individual match observations of 42 outfield players (goalkeepers excluded) from the Brazilian national leagues were analyzed. The players were categorized into four positions: central defenders (n = 10), full-backs (n = 9), midfielders (n = 14), and forwards (n = 9). The following running variables were retained: total distance (TD), walking (0 to 6 km·h-1), jogging (6.1 to 12 km·h-1), low (LIR: 12.1 to 15 km·h-1), medium (MIR: 15.1 to 19 km·h-1), and high intensity running (HIR: 19.1 to 23 km·h-1), sprint (> 23 km·h-1), and high intensity activity (HIA: sum of MIR + HIR + sprint). Overall, drawing status decreased distances walking and increased TD, jogging, LIR, MIR, HIR, and HIA compared to winning and losing status. Forwards and full-backs covered greater sprint distance during drawing than losing status. Central defenders accumulated less sprint distances during drawing and winning conditions than other positions. Lastly, full-backs and forwards when drawing and winning, respectively, covered longer sprint distances than midfielders. These findings may help coaches to better understand the influence of contextual factors on running performance of Brazilian elite-level soccer players, in addition to offering relevant information for the development of individualized training programs